Perkembangan Ekonomi Digital Terhadap Pertumbuhan Ekonomi Daerah Bali - Dewa Gde Yoga Permana; I Gede Bayu Wirayudha (Jurnal Riset dan Inovasi Manajemen, 2023)
The Digital Economy Era must be utilized for the economy, especially the regional economy, it appears that regional economic development is somewhat difficult to develop because it still uses a traditional economic system. However, not all regions are willing to utilize digital payment systems for various reasons, especially business actors in traditional markets. The aim of this research is to look at the development of the digital economy on regional economic growth in the province of Bali. The method used in this research uses descriptive analysis to determine the impact and influence of digital payments on economic growth in the Bali region. Starting from looking at economic growth in Bali before using digital-based payments, and finally looking at economic growth in Bali after the digital payment system, especially in traditional markets. The results of this research show that there is an influence of digital payment systems on economic growth in the regions, with the many conveniences provided in digital payments making business actors in the regions prefer digital payment systems in transactions. The conclusion of this research is that increasing the income of local business actors who use automatic digital payment systems also increases regional income in Bali.